PERANCANGAN PASAR RAKYAT DI KECAMATAN BEDUAI - Haque, Firdaus Alfarizi Dienul; Kalsum, Emilya; Putro, Jawas Dwijo (Program Studi Arsitektur Fakultas Teknik Universitas Tanjungpura, 2022)
The market is a place where the place is intended as a place to meet sellers and buyers to carry out buying and selling activities of various consumer goods by conducting a bargaining process. The people's market is important for the economy, social and welfare of the people. The people's market besides having a major role in economic activity, also has other roles such as in a social role. Beduai sub-district is located in Sanggau district, West Kalimantan, this certainly does not escape social and economic activities. So far, traders are still having trouble finding a place to sell their wares because there are no people's market facilities in this sub-district. Therefore, it is necessary to build people's market facilities to meet the needs of the community, besides that the existence of the people's market also provides a place for traders, especially when the harvest season arrives. The design of the people's market in Beduai sub-district is an idea in solving community problems in meeting their daily needs, as well as economic activities that still depend on other sub-districts. Various problems that we often encounter in people's markets such as slums, dirty, muddy, smelly, and stuffy. The resolution of these problems is solved by the design method using five stages which include; initiation, preparation, proposal submission, evaluation and action.